MAGIC: once upon a time in consent management$da FHIR® tale - Bialke, Martin; Tremper, Galina; Lablans, Martin; Ückert, Frank (Journal of translational medicine, 2018)
The use of medical data for research purposes requires an informed consent of the patient that is compliant with the EU General Data Protection Regulation. In the context of multi-centre research initiatives and a multitude of clinical and epidemiological studies scalable and automatable measures for digital consent management are required. Modular form, structure, and contents render a patient’s consent reusable for varying project settings in order to effectively manage and minimise organisational and technical efforts.